Ensuring safe water in post-chemical, biological, radiological and nuclear emergencies - Praveen Kumar Amar (Wolters Kluwer Medknow Publications, 2010)
Disaster scenarios are dismal and often result in mass displacement and migration of people. In eventuality of emergency situations, people need to be rehabilitated and provided with an adequate supply of drinking water, the most essential natural resource needed for survival, which is often not easily available even during non-disaster periods. In the aftermath of a natural or human-made disaster affecting mankind and livestock, the prime aim is to ensure supply of safe water to reduce the occurrence and spread of water borne disease due to interrupted, poor and polluted water supply. Chemical, biological, radiological and nuclear (CBRN) emergencies augment the dilemma as an additional risk of "contamination" is added. The associated risks posed to health and life should be reduced to as low as reasonably achievable. Maintaining a high level of preparedness is the crux of quick relief and efficient response to ensure continuous supply of safe water, enabling survival and sustenance. The underlying objective would be to educate and train the persons concerned to lay down the procedures for the detection, cleaning, and treatment, purification including desalination, disinfection, and decontamination of water. The basic information to influence the organization of preparedness and execution of relief measures at all levels while maintaining minimum standards in water management at the place of disaster, are discussed in this article.